The Implementation of Learning Physics with the STEM-PBL Approach to Newton's Law Materials and its Application for Character Development - Yulianti, Dwi; Masiroh, Fafi (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2024)
Globalization in the 21st Century era has the opportunity to cause a decline in character. The government tries to strengthen student character through the Pancasila Student Profile. STEM (Science, Technology, Engineering, and Mathematics) based learning can facilitate student’s character. This study aims to describe the implementation of physics learning with STEM and its effect on student learning outcomes and character development. The research design employed was quasi-experimental, and the research sampling technique used was purposive sampling to determine two classes of tenth-grade students of MA Al Anwar Sarang. The experimental class integrated the STEM approach into each learning activity, and the control class used the scientific approach. Student character development was measured using observation sheets, and student learning outcomes were assessed by analyzing pretest and post-test scores. The findings of this study highlight the potential of integrating the STEM approach with Problem-Based Learning (PBL) to effectively teach Newton's Laws and develop student character. The medium-level improvement in learning outcomes (gain n = 0.399) and the high percentage of Pancasila student profile character development (81.33%) indicate that STEM-based physics learning supports academic and character-building objectives. These results suggest that optimizing all aspects of STEM integration, from learning tools to activities, is essential for fostering student character development in alignment with the Pancasila student profile. Additionally, implementing STEM-based physics learning sustainably over an extended period is recommended to enhance long-term learning outcomes and character formation